A pH / temperature dual-responsive nanocomposite coagulant, a preparation method thereof and application thereof in oily wastewater treatment

CN121377272BActive Publication Date: 2026-10-27陕西榆大科技发展有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511580500.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-10-27
Estimated Expiration
2045-10-31

AI Technical Summary

Technical Problem

传统含油含尘废水处理技术存在四大瓶颈:(1)药剂消耗占运营成本40%以上,铝盐凝聚剂等不可回收,导致处理成本高;(2)pH或温度波动导致破乳效率下降,环境适合应性差;(3)对粒径<50μm的乳化油去除率不足70%,微油滴去除效果不佳;(4)缺乏吸附油滴的资源化回收机制,造成二次污染和资源浪费等难题

Benefits of technology

[0020]1、本发明以Fe3O4纳米颗粒为原料,在SiO2绝缘层中嵌入GQDs,制备核壳结构Fe3O4@SiO2-GQDs,其表面接枝MPS后,通过自由基聚合构建温敏性PNIPAM与pH响应型PAAc的互穿网络(IPN)结构,形成“磁核-绝缘层-IPN智能层”三级体系的pH/温度双响应的纳米复合凝聚剂。通过嵌入GQDs的SiO2绝缘层保护和PNIPAM/PAAc互穿网络的双响应机制,使凝聚剂在pH=3~10的环境中仍能保持95%以上的磁回收率,且循环5次后磁饱和强度衰减率<5%,展现出卓越的环境适应性与稳定性;将最低临界溶解温度稳定控制在32±0.5℃,确保材料在20~80℃温度波动范围内的稳定性能,同时通过PAAc的羧基电离使材料在pH>7时聚合物链伸展,吸附容量显著提升,对碱性含油废水保持≥97%的高效破乳能力,并在温度>32℃时通过PNIPAM疏水塌缩驱动油滴聚并,絮凝效率≥97%;凭借IPN智能网络的纳米级协同效应,对<50μm微油滴捕获能力提升30%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121377272B_ABST
    Figure CN121377272B_ABST
Patent Text Reader

Abstract

The application discloses a pH / temperature dual-response nano composite coagulant, a preparation method thereof and application of the nano composite coagulant in oil-containing wastewater treatment. Fe3O4 nanoparticles are used as raw materials, GQDs are embedded in a SiO2 insulation layer, a core-shell structure Fe3O4@SiO2-GQDs is prepared, the surface of the Fe3O4@SiO2-GQDs is grafted with 3-(methacryloyloxy)propyl trimethoxysilane, and then a temperature-sensitive PNIPAM and a pH-responsive PAAc interpenetrating network (IPN) structure is constructed through free radical polymerization, so that a pH / temperature dual-response nano composite coagulant with a'magnetic core-insulation layer-IPN intelligent layer' three-level system is formed. When pH>7, the PAAc carboxyl group of the coagulant is ionized, and the adsorption capacity is significantly improved. When the temperature is greater than 32 DEG C, the PNIPAM hydrophobic collapse, and the flocculation efficiency is greater than or equal to 97%. After magnetic recovery, the pH is adjusted to be less than 7 and the temperature is less than 32 DEG C to release the adsorbed oil droplets. The magnetic core is regenerated through microwave irradiation, and the magnetic saturation strength attenuation rate is less than 5% after 5 cycles. The application solves the problems of single function, non-recovery and poor environmental adaptability of the traditional coagulant, and is suitable for efficient treatment of oil-containing wastewater such as mechanical machining emulsion, oilfield produced water and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of environmental functional materials technology, specifically relating to a smart responsive nanocomposite coagulant, its preparation method and application, which is particularly suitable for the treatment of industrial oily wastewater. Background Technology

[0002] Industrial oily and dusty wastewater accounts for 18% of the total industrial wastewater due to its high COD, difficulty in degradation, and easy emulsification. Traditional oily and dusty wastewater treatment technologies have four major bottlenecks: (1) Reagent consumption accounts for more than 40% of the operating cost, and aluminum salt coagulants and other non-recyclable agents lead to high treatment costs; (2) pH or temperature fluctuations lead to a decrease in demulsification efficiency and poor environmental adaptability; (3) The removal rate of emulsified oil with a particle size <50μm is less than 70%, and the removal effect of micro oil droplets is not good; (4) There is a lack of resource recovery mechanism for adsorbed oil droplets, which causes problems such as secondary pollution and resource waste.

[0003] Existing magnetic nano-coagulants generally suffer from technical bottlenecks such as insufficient surface active sites, lack of intelligent responsiveness, and easy oxidation of the magnetic core. For example, CN120328702A developed a flocculant with oil and dust removal functions by doping magnetic cellulose, but the following significant defects were found in practical applications: First, the material did not construct a pH / temperature responsive structure, and could not autonomously adjust its surface properties according to changes in operating temperature or pH fluctuations; second, the modification effect of nano-TiO2 was unstable, and the magnetic properties rapidly decayed during recycling, and the magnetic cellulose loading was limited, resulting in insufficient magnetic response intensity and a sharp drop in recovery rate in high-speed airflow dust removal scenarios; in addition, the chitosan component in the material was prone to degradation in strong acid (pH<3) or strong oxidizing environments, leading to the collapse and failure of the overall structure. These defects severely restrict the application effect of this material in complex industrial environments.

[0004] Thermosensitive polymers lack magnetic recovery capabilities and exhibit poor adsorption at low temperatures. For example, CN119978267A discloses a thermosensitive nanomaterial and its preparation method, as well as an oil displacement agent containing this material and its application. Although this technology successfully prepares thermosensitive nanomaterials with oil and dust removal functions, it still has limitations in practical applications. First, the material's lowest critical solution temperature (LCST) is 69.8℃, which is not compatible with the oil and dust removal requirements under normal temperature conditions. Second, its pH response range is limited to alkaline environments (pH>7), making it difficult to meet the treatment needs of acidic environments (pH 3-5) such as coal-fired flue gas. Furthermore, under high salinity conditions, the polymer hydration layer on the material surface is easily damaged, leading to the failure of its thermosensitive properties. In terms of material structure, due to the lack of magnetic components, efficient magnetic separation and recovery cannot be achieved. At the same time, the mechanical strength of the pure SiO2-based core is insufficient, and the surface polymer layer is prone to peeling off during recycling, affecting the material's service life and performance stability.

[0005] In summary, existing technologies suffer from the following contradictions: "functional limitation, difficulty in recycling, environmental sensitivity, and lack of resource utilization": materials only respond to single pH or temperature stimuli and cannot adapt to complex working conditions; magnetic materials experience capacity decay after repeated use, and magnetic nuclei are oxidized when pH > 8; thermosensitive polymers are permanently deactivated at > 40℃, and pH fluctuations cause irreversible phase transitions. Summary of the Invention

[0006] The purpose of this invention is to provide a pH / temperature dual-responsive, recyclable, and environmentally adaptable nanocomposite coagulant and its preparation method.

[0007] The pH / temperature dual-responsive nanocomposite coagulant provided by this invention comprises an Fe3O4 magnetic core, a SiO2 insulating layer embedded with graphene quantum dots, and a poly(N-isopropylacrylamide) / polyacrylic acid interpenetrating polymer network layer, with a particle size of 180–250 nm and a magnetic saturation strength ≥45 emu / g. It is prepared by the following steps:

[0008] Step 1: Disperse Fe3O4 nanoparticles in ethanol, add tetraethyl orthosilicate, ammonia and graphene quantum dots (GQDs), and stir the reaction at pH 8-10 and temperature 40-50℃ for 4-8 hours to coat the surface of Fe3O4 nanoparticles with a SiO2 insulating layer embedded with GQDs; after the reaction is complete, magnetically separate the product, wash with ethanol and water alternately, and vacuum dry to obtain core-shell structured Fe3O4@SiO2-GQDs nanoparticles.

[0009] Step 2: The core-shell structured Fe3O4@SiO2-GQDs nanoparticles were uniformly dispersed in ethanol, and 3-(methacryloyloxy)propyltrimethoxysilane (MPS) was added. The mixture was refluxed at 60-80°C under nitrogen protection for 10-15 hours. After the reaction was completed, the product was magnetically separated, washed with ethanol, and vacuum dried to obtain the Fe3O4@SiO2-GQDs-MPS composite material with double bonds on its surface.

[0010] Step 3: Dissolve N-isopropylacrylamide (NIPAM), acrylic acid (AAc), N,N'-methylenebisacrylamide (MBA), and azobisisobutyronitrile (AIBN) in water, add Fe3O4@SiO2-GQDs-MPS composite material with double bonds on its surface, and ultrasonically disperse evenly. Stir and react at 60-80℃ for 6-10 hours under nitrogen protection. Coat the surface of the composite material with a poly(N-isopropylacrylamide) / polyacrylic acid (PNIPAM / PAAc) interpenetrating network polymer layer. After the reaction is complete, magnetically separate the product, wash with warm water, and freeze-dry to obtain a pH / temperature dual-responsive nanocomposite coagulant.

[0011] In step 1 above, the preferred feeding ratio of Fe3O4 nanoparticles, tetraethyl orthosilicate, ammonia and GQDs is 1g:4-5mL:3-4mL:0.015-0.025g; the mass concentration of the ammonia is 25%-30%.

[0012] In step 1 above, the preferred particle size of the Fe3O4 nanoparticles is 20±5nm, the thickness of the SiO2 insulating layer embedded with GQDs is 30±5nm, and the particle size of the GQDs is 3~5nm.

[0013] In step 1 above, the GQDs content in the insulating layer is preferably 0.5% to 2% of the mass of SiO2.

[0014] In step 2 above, the preferred feeding ratio of the core-shell structured Fe3O4@SiO2-GQDs nanoparticles to MPS is 1g:0.2-0.3mL.

[0015] In step 3 above, the preferred molar ratio of NIPAM to AAc is 1:0.8 to 1.2, the amount of MBA is 1.5% to 2% of the total molar amount of NIPAM and AAc, and the amount of AIBN is 1% to 5% of the total molar amount of NIPAM and AAc.

[0016] Furthermore, in step 3 above, the preferred ratio of the amount of Fe3O4@SiO2-GQDs-MPS composite material with surface rich in double bonds to the total mass of NIPAM and AAc is 1:0.6 to 1.5.

[0017] In step 3 above, the preferred temperature for the warm water washing is 35-40°C, which is higher than the LCST (32°C) of PNIPAM.

[0018] This invention also provides the application of the above-mentioned pH / temperature dual-responsive nanocomposite coagulant in the treatment of oily wastewater.

[0019] The beneficial effects of this invention are as follows:

[0020] 1. This invention uses Fe3O4 nanoparticles as raw materials to embed GQDs in a SiO2 insulating layer to prepare core-shell structure Fe3O4@SiO2-GQDs. After grafting MPS onto its surface, an interpenetrating network (IPN) structure of temperature-sensitive PNIPAM and pH-responsive PAAc is constructed through free radical polymerization, forming a pH / temperature dual-responsive nanocomposite coagulant of a three-level system of "magnetic core-insulating layer-IPN smart layer". By employing a SiO2 insulating layer embedded with GQDs and a dual-response mechanism of PNIPAM / PAAc interpenetrating network, the coagulant maintains a magnetic recovery rate of over 95% in environments with pH values ​​of 3–10, and exhibits a magnetic saturation intensity decay rate of <5% after 5 cycles, demonstrating excellent environmental adaptability and stability. The minimum critical dissolution temperature is stably controlled at 32±0.5℃, ensuring stable performance within a temperature fluctuation range of 20–80℃. Simultaneously, the carboxyl ionization of PAAc causes polymer chain extension at pH > 7, significantly enhancing adsorption capacity. It maintains a high-efficiency demulsification capacity of ≥97% for alkaline oily wastewater, and at temperatures > 32℃, oil droplet aggregation is driven by PNIPAM hydrophobic collapse, achieving a flocculation efficiency of ≥97%. Furthermore, thanks to the nanoscale synergistic effect of the IPN intelligent network, the capture capacity for <50μm micro-oil droplets is improved by 30%.

[0021] 2. This invention employs a Fe3O4@SiO2-GQDs magnetic core-insulating layer structure, achieving over 95% efficient recovery within 10 minutes under a 0.3T magnetic field. Compared to traditional non-recoverable coagulants such as polyaluminum chloride, this significantly reduces reagent consumption and sludge generation. The unique SiO2 insulating layer design effectively blocks the oxidation of the Fe3O4 magnetic core. Microwave radiation regeneration technology (300W, 2min) allows the material to maintain over 95% adsorption capacity even after 5 reuses, significantly reducing costs.

[0022] 3. This invention innovatively constructs an intelligent closed loop of "adsorption-release-resource recovery": the IPN network synchronously responds to pH / temperature signals, and the coagulant adsorbs pollutants when pH > 7 or temperature > 32℃; after magnetic recovery, the pH is adjusted to < 7 and the temperature to < 32℃ to release the adsorbed oil droplets, achieving resource recovery. This coagulant can flexibly cope with different working conditions such as high-temperature alkaline emulsions and low-temperature acidic oily wastewater. This dual environmental response mechanism breaks through the limitations of traditional single-response technology, providing an intelligent solution for the treatment of complex industrial wastewater. It also successfully overcomes the technical bottlenecks of traditional coagulants, such as single function, low recovery efficiency, and difficulty in resource recovery. It is particularly suitable for the efficient treatment and resource recovery of oily wastewater such as machining emulsions and oilfield produced water.

[0023] 4. This invention fundamentally solves the problem of aluminum residue pollution from traditional aluminum salt coagulants. Its non-toxic and biodegradable properties fully meet modern environmental protection requirements, completely replacing traditional single-use agents such as aluminum salts, and eliminating aluminum residue and sludge generation at the source. The unique microwave radiation regeneration technology replaces high-consumption chemical regeneration, achieving efficient recovery and resource utilization of ≥97% of adsorbed oil droplets while ensuring 95% adsorption capacity of the material. The entire process produces no toxic waste emissions, successfully breaking through the closed-loop technology barrier of "treatment-recovery-resource utilization," and providing a sustainable and intelligent solution for industrial oily wastewater. Attached Figure Description

[0024] Figure 1 This is a SEM image of Fe3O4 from Example 1.

[0025] Figure 2 This is a SEM image of the Fe3O4@SiO2-GQDs prepared in Example 1.

[0026] Figure 3 This is a SEM image of the Fe3O4@SiO2-GQDs-IPN composite material prepared in Example 1. Detailed Implementation

[0027] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the scope of protection of the present invention is not limited to these embodiments.

[0028] Example 1

[0029] Step 1: Take 10.0 g of Fe3O4 nanoparticles with a particle size of 20 nm, add 500 mL of anhydrous ethanol, and ultrasonically disperse at 300 W for 30 min; then add 42.4 mL of tetraethyl orthosilicate, 35.7 mL of 28% ammonia solution, and 0.21 g of GQDs (particle size 3-5 nm, accounting for 1.5% of the theoretical mass of SiO2), maintain pH = 9.0 ± 0.2, and stir at 45 °C (600 rpm) for 6 h to coat the surface of Fe3O4 nanoparticles with an embedded SiO2 insulating layer of GQDs. After the reaction, magnetically separate the product, wash with alternating ethanol / water three times, and vacuum dry at 60 °C for 12 h to obtain core-shell structured Fe3O4@SiO2-GQDs nanoparticles (see...). Figure 2 The coating thickness of SiO2-GQDs is 30 nm.

[0030] Step 2: 10.0 g of Fe3O4@SiO2-GQDs nanoparticles were uniformly dispersed in 300 mL of anhydrous ethanol, followed by the addition of 2.38 mL of MPS as a surface modifier. The reaction was carried out under nitrogen protection at 70 °C under constant reflux for 12 h. After the reaction was completed, the product was collected using magnetic separation technology and washed three times with anhydrous ethanol to completely remove the physically adsorbed MPS molecules. Finally, the modified material was dried in a vacuum drying oven at 60 °C for 6 h to obtain a Fe3O4@SiO2-GQDs-MPS composite material with a surface rich in double bonds.

[0031] Step 3: Dissolve 6.95 g (61.4 mmol) NIPAM, 3.61 g (50 mmol) AAc, 0.308 g (2 mmol) MBA, and 0.246 g (1.5 mmol) AIBN in 200 mL of deionized water. Add 10.0 g of Fe3O4@SiO2-GQDs-MPS composite material with a surface rich in double bonds, and ultrasonically disperse until uniform. React at 65 °C with stirring (300 rpm) for 8 h under nitrogen protection. Coat the surface of the composite material with a PNIPAM / PAAc interpenetrating network (IPN) polymer layer. After the reaction, magnetically separate the product, wash three times with 35 °C warm water to remove free polymer, and freeze-dry to obtain Fe3O4@SiO2-GQDs-IPN coagulant (see...). Figure 3 Its particle size is 215±10nm.

[0032] Comparative Example 1

[0033] Step 1: Take 10.0 g of Fe3O4 nanoparticles with a particle size of 20 nm, add 500 mL of anhydrous ethanol, and ultrasonically disperse at 300 W for 30 min; then add 42.4 mL of tetraethyl orthosilicate and 35.7 mL of 28% ammonia solution, maintain pH = 9.0 ± 0.2, and react at 45 °C with stirring (600 rpm) for 6 h to coat the surface of the Fe3O4 nanoparticles with a SiO2 insulating layer. After magnetic separation, wash with alternating ethanol / water three times, and vacuum dry at 60 °C for 12 h to obtain core-shell structured Fe3O4@SiO2 nanoparticles with a SiO2 coating thickness of 30 nm.

[0034] Step 2: 10.0 g of Fe3O4@SiO2 nanoparticles were uniformly dispersed in 300 mL of anhydrous ethanol, followed by the addition of 2.38 mL of MPS as a surface modifier. The mixture was refluxed at 70 °C for 12 h under nitrogen protection. After the reaction was complete, the product was collected using magnetic separation technology and washed three times with anhydrous ethanol to completely remove physically adsorbed MPS molecules. Finally, the modified material was dried in a vacuum drying oven at 60 °C for 6 h to obtain a Fe3O4@SiO2-MPS composite material with a surface rich in double bonds.

[0035] Step 3: Dissolve 6.95 g (61.4 mmol) NIPAM, 0.308 g (2 mmol) MBA, and 0.246 g (1.5 mmol) AIBN in 200 mL of deionized water. Add 10.0 g of Fe3O4@SiO2-MPS composite material with double bonds on its surface, and ultrasonically disperse until uniform. React under nitrogen protection at 65 °C with stirring (300 rpm) for 8 h to coat the surface of the composite material with PNIPAM. After the reaction, magnetically separate the product, wash three times with 35 °C warm water to remove free polymer, and freeze-dry to obtain Fe3O4@SiO2-PNIPAM coagulant.

[0036] Application Example 1

[0037] Oily wastewater treatment: Fe3O4@SiO2-GQDs-IPN coagulant prepared in Example 1 was added to 10L of machining emulsion with an oil content of 1250mg / L at a concentration of 0.5g / L. The pH of the system was adjusted to 9.0 with 1mol / L sodium hydroxide aqueous solution. The mixture was stirred at 35℃ for 1h and then allowed to stand for 1h. The oil content of the effluent was tested, and the oil removal rate and adsorption capacity were calculated. The test showed that the oil content of the effluent decreased to 9.5mg / L (oil removal rate 99.2%), and the coagulant adsorption capacity reached 2481mg / g. Subsequently, the coagulant was magnetically separated and recovered using a 0.3T magnetic field for 10min. The recovered coagulant was placed in a beaker containing 50mL of deionized water, and the pH was adjusted to 6.0 with 1mol / L hydrochloric acid solution. The mixture was stirred at room temperature (25℃) for 1h to release the adsorbed oil droplets. After the oil droplets were released, the coagulant was regenerated by microwave radiation (300W, 2min). The regenerated coagulant was recycled 5 times using the method described above. After each cycle, its magnetic saturation intensity was measured and the attenuation rate relative to the first use was calculated. At the same time, the oil content, oil removal rate and adsorption capacity of the effluent were recorded. The specific results are shown in Table 1.

[0038] Table 1

[0039] The Fe3O4@SiO2-PNIPAM coagulant prepared in Comparative Example 1 was used in a comparative experiment according to the above method. The results showed that after the first treatment, the oil content in the effluent decreased to 250 mg / L (oil removal rate of 80%), and the adsorption capacity was 2000 mg / g. The coagulant was magnetically separated and recovered using a 0.3T magnetic field for 10 min. The recovered coagulant was then recycled 5 times. Each time, the oil content in the effluent, oil removal rate, adsorption capacity, magnetic saturation intensity, and decay rate were measured. The results are shown in Table 2.

[0040] Table 2

[0041] Comparing the data in Tables 1 and 2, it is evident that the Fe3O4@SiO2-GQDs-IPN coagulant prepared in this invention outperforms the Fe3O4@SiO2-PNIPAM coagulant in Comparative Example 1, which is undoped with GQDs and contains only a PNIPAM single network, in terms of oil removal rate, adsorption capacity, magnetic saturation retention rate, and cycle stability. Specifically, GQDs doping significantly enhances the interfacial conductivity and structural stability of the material, contributing to improved magnetic response performance and magnetic saturation retention rate during cycling. Therefore, the magnetic saturation decay rate of Fe3O4@SiO2-GQDs-IPN after 5 cycles is only 3.5%, far lower than the 16.3% of the material in Comparative Example 1. The IPN structure formed by PNIPAM and PAAc endows the material with dual pH / temperature response characteristics, extending to enhance adsorption under alkaline high-temperature conditions and contracting to promote desorption under acidic room-temperature conditions, thereby improving the adsorption capacity and regeneration efficiency of the material and achieving efficient and controllable oil-water separation and material recycling.

[0042] Application Example 2

[0043] Comparison of operating conditions: 10L each of different oily wastewater (oilfield produced water, catering waste oil emulsion, and cold rolling emulsion) were taken, and Fe3O4@SiO2-GQDs-IPN coagulant prepared in Example 1 was added at a dosage of 0.5g / L. The pH and temperature were adjusted with hydrochloric acid or sodium hydroxide, and the mixture was stirred for 1 hour and then allowed to stand for 1 hour. The oil content of the effluent was tested, and the oil removal rate and adsorption capacity were calculated. The results are shown in Table 3.

[0044] Table 3

[0045] The Fe3O4@SiO2-PNIPAM coagulant prepared in Comparative Example 1 was subjected to a comparative experiment using the method described above. The results are shown in Table 4.

[0046] Table 4

[0047] Comparing the data in Tables 3 and 4, it can be seen that the Fe3O4@SiO2-GQDs-IPN coagulant prepared in this invention exhibits higher oil removal rate and adsorption capacity under different pH and temperature conditions, and has stronger environmental adaptability.

Claims

1. A method for preparing a pH / temperature dual-responsive nanocomposite coagulant, characterized in that... Includes the following steps: Step 1: Disperse Fe3O4 nanoparticles in ethanol, add tetraethyl orthosilicate, ammonia and graphene quantum dots, and stir the reaction at pH 8-10 and temperature 40-50℃ for 4-8 hours to coat the surface of Fe3O4 nanoparticles with a SiO2 insulating layer embedded with graphene quantum dots; after the reaction is complete, magnetically separate the product, wash with ethanol and water alternately, and vacuum dry to obtain core-shell structured Fe3O4@SiO2-GQDs nanoparticles; Step 2: The core-shell structured Fe3O4@SiO2-GQDs nanoparticles were uniformly dispersed in ethanol, and 3-(methacryloyloxy)propyltrimethoxysilane was added. The mixture was refluxed at 60-80°C for 10-15 hours under nitrogen protection. After the reaction was completed, the product was magnetically separated, washed with ethanol, and vacuum dried to obtain Fe3O4@SiO2-GQDs-MPS composite material with double bonds on the surface. Step 3: Dissolve N-isopropylacrylamide, acrylic acid, N,N′-methylenebisacrylamide and azobisisobutyronitrile in water, add Fe3O4@SiO2-GQDs-MPS composite material with double bonds on the surface, ultrasonically disperse evenly, and stir and react at 60-80℃ for 6-10 hours under nitrogen protection. Coat the surface of the composite material with a poly(N-isopropylacrylamide) / polyacrylic acid interpenetrating network polymer layer. After the reaction is complete, magnetically separate the product, wash with warm water, freeze dry, and obtain a pH / temperature dual-responsive nanocomposite coagulant.

2. The method for preparing the pH / temperature dual-responsive nanocomposite coagulant according to claim 1, characterized in that: The feeding ratio of Fe3O4 nanoparticles, tetraethyl orthosilicate, ammonia, and graphene quantum dots is 1g:4-5mL:3-4mL:0.015-0.025g; the mass concentration of the ammonia is 25%-30%.

3. The method for preparing the pH / temperature dual-responsive nanocomposite coagulant according to claim 1, characterized in that: In step 1, the content of graphene quantum dots in the insulating layer is 0.5% to 2% of the mass of SiO2.

4. The method for preparing the pH / temperature dual-responsive nanocomposite coagulant according to claim 1, characterized in that: In step 1, the Fe3O4 nanoparticles have a particle size of 20±5nm, the SiO2 insulating layer with embedded graphene quantum dots has a thickness of 30±5nm, and the graphene quantum dots have a particle size of 3-5nm.

5. The method for preparing the pH / temperature dual-responsive nanocomposite coagulant according to claim 1, characterized in that: In step 2, the feeding ratio of the core-shell structured Fe3O4@SiO2-GQDs nanoparticles to 3-(methacryloyloxy)propyltrimethoxysilane is 1g:0.2-0.3mL.

6. The method for preparing the pH / temperature dual-responsive nanocomposite coagulant according to claim 1, characterized in that: In step 3, the molar ratio of N-isopropylacrylamide to acrylic acid is 1:0.8 to 1.2, the amount of N,N′-methylenebisacrylamide used is 1.5% to 2% of the total molar amount of N-isopropylacrylamide and acrylic acid, and the amount of azobisisobutyronitrile used is 1% to 5% of the total molar amount of N-isopropylacrylamide and acrylic acid.

7. The method for preparing the pH / temperature dual-responsive nanocomposite coagulant according to claim 1, characterized in that: In step 3, the ratio of the amount of Fe3O4@SiO2-GQDs-MPS composite material with double bonds on its surface to the total mass of N-isopropylacrylamide and acrylic acid is 1:0.6 to 1.

5.

8. The method for preparing the pH / temperature dual-responsive nanocomposite coagulant according to claim 1, characterized in that: In step 3, the temperature of the warm water washing is 35-40℃.

9. The pH / temperature dual-responsive nanocomposite coagulant obtained by the preparation method according to any one of claims 1 to 8, comprising an Fe3O4 magnetic core, a SiO2 insulating layer embedded with graphene quantum dots, and a poly(N-isopropylacrylamide) / polyacrylic acid interpenetrating network polymer layer, having a particle size of 180-250 nm and a magnetic saturation strength ≥45 emu / g.

10. The application of the pH / temperature dual-responsive nanocomposite coagulant of claim 9 in the treatment of oily wastewater.

Citation Information

Patent Citations

  • Temperature-sensitive nano material, preparation method thereof, oil-displacing agent and application of oil-displacing agent

    CN119978267A

  • Flocculating agent doped with magnetic cellulose and preparation method thereof

    CN120328702A

  • Preparation method and application of magnetic nanometer flocculant suitable for emulsified oil waste water treatment

    CN109052596A

  • Fluorescent / pH / temperature-sensitive / magnetic multi-response nanogel carrier and preparation method thereof

    CN112516332A